2019
DOI: 10.3390/nu11051186
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Strategies to Prevent Lens Cataract: Current Status and Future Strategies

Abstract: Oxidative stress and the subsequent oxidative damage to lens proteins is a known causative factor in the initiation and progression of cataract formation, the leading cause of blindness in the world today. Due to the role of oxidative damage in the etiology of cataract, antioxidants have been prompted as therapeutic options to delay and/or prevent disease progression. However, many exogenous antioxidant interventions have to date produced mixed results as anti-cataract therapies. The aim of this review is to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 99 publications
1
52
0
8
Order By: Relevance
“…By MRI imaging, it was demonstrated that the lens has a unique internal microcirculation system to deliver antioxidants in different regions, and sodium is important in this mechanism [13]. In both groups treated only with Prednison, the serum level of ionic sodium was significantly increase (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…By MRI imaging, it was demonstrated that the lens has a unique internal microcirculation system to deliver antioxidants in different regions, and sodium is important in this mechanism [13]. In both groups treated only with Prednison, the serum level of ionic sodium was significantly increase (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 98%
“…It seems that steroids do not directly act on the lens but rather produce an imbalance of ocular cytokines and growth factors [12]. Recently, it was demonstrated that distinct metabolic compartments exist in the lens and these explains different etiologies of nuclear and cortical cataract, even the one induced by Prednison [13].…”
Section: Resultsmentioning
confidence: 99%
“…However, with increasing age, GSH is known to decrease specifically in the lens nucleus [ 46 ], rendering proteins in this region susceptible to oxidative damage. Because of the proven association between lens cataract and oxidative damage, antioxidant supplementation has been promoted as a treatment strategy to slow down the progression of this type of cataract [ 6 , 7 , 8 ].…”
Section: Aetiology Of the Different Types Of Cataractmentioning
confidence: 99%
“…Given the protective effects of vitamin C in the lens and the link between a decrease in vitamin C with increasing age and with increasing cataract severity [ 11 ], it is not surprising that numerous studies exist investigating the relationship between vitamin C and the risk of cataract. While there a number of excellent in depth reviews on vitamin supplementation, diet, and cataract in human populations [ 7 , 8 , 81 , 82 , 83 , 84 , 85 ], reviews summarizing the findings from animal studies are lacking. However, these studies are important as they should be used to help inform and guide the design of human therapeutic studies.…”
Section: Evidence Of the Effects Of Vitamin C On Cataract Preventimentioning
confidence: 99%
See 1 more Smart Citation